Can Collaboration Between Nonprofit Hospitals and Local Health Departments Influence Population Health Investments by Nonprofit Hospitals?. (23rd August 2021) - Santos, Tatiane; Lee, Shoou-Yih D.; East, Chloe; Lindrooth, Richard C.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The patient protection and Affordable Care Act (ACA) sought to improve population health by requiring nonprofit hospitals (NFPs) to conduct triennial community health needs assessments and address the identified needs. In this context, some states have encouraged collaboration between hospitals and local health department (LHD) to increase the focus of community benefit spending onto population health. Objectives: The aim was to examine whether a 2012 state law that required NFPs to collaborate with LHDs in local health planning influenced hospital population health improvement spending. Research Design: We merged Internal Revenue Service data on NFP community benefit spending with data on hospital, county and state-level characteristics and estimated a difference-in-differences specification of hospital population health spending in 2009–2016 that compared the difference between hospitals that were required to collaborate with LHDs to those that were not, before and after the requirement. Measures: The primary outcome was population health spending divided by operating expenses. Results: We found that the requirement for hospital-LHD collaboration was associated with increased mean population health spending of ∼$393, 000–$786, 000 ( P =0.03). This association was significant in 2015–2016, perhaps reflecting the lag between assessments and implementation. Urban hospitals were responsible for most of the increased spending. Conclusions: Policymakers have sought to encourage hospitals to increase their investment in population health; however, overall community benefit spending on population health has remained flat. We found that requiring hospital-LHD collaboration was associated with increased hospital investment in population health. It may be that hospitals increase population health spending because collaboration improves expected effectiveness or increases hospital accountability.